A fully decentralized approach for mitigating destructive disturbances in isolating process of remote coupled microgrids - Pashajavid, E.; Ghosh, Arindam (2016)
Coupling remote microgrids (MGs) is a promising technique to handle power deficiency in such systems. However, once the shortfall is removed, the coupled MGs (CMG) should isolate to carry on their operation autonomously. Due to the non-zero power still flowing through the tie-line, however, considerable voltage spikes may be imposed on the interconnecting static switch (ISS) during the isolation that may damage the device. This paper proposes a practical decentralized approach to efficiently alleviate the mentioned transients, facilitating a successful MG isolation procedure. Two auxiliary controllable loads (ACL) are to be considered at two sides of the ISS. When the necessity of applying the isolation action is detected, the ISS controller commands the ACL on the supporting MG side to connect. A droop-based scheme is formulated to derive the load should be demanded by the ACL such that the power passing through the ISS drops to zero, preventing any spikes across it at the opening moment. Once the isolation action is accomplished, the controller disconnects the ACL. Efficiency of the proposed algorithm is validated through various cases simulated using PSCAD/EMTDC.